2022
DOI: 10.1080/21645515.2022.2035142
|View full text |Cite
|
Sign up to set email alerts
|

Resolving sex and gender bias in COVID-19 vaccines R&D and beyond

Abstract: The influence of sex and gender in immune response and vaccine outcomes is established in many disease areas, including in COVID-19. Yet, there are notable gaps in the consideration of sex and gender in the analysis and reporting of COVID-19 vaccines clinical trial data. The push for stronger sex and gender integration in vaccines science should be championed by all researchers and stakeholders across the R&D and access ecosystem – not just gender experts. This requires joint action on the tactical framing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Sex and gender are important factors in understanding the real-world effectiveness of vaccines and postmarketing safety monitoring [ 45 , 46 ]. Sex and gender differences in vaccine hesitancy and immunization outcomes have been observed for COVID-19 and other vaccine-preventable diseases, with women typically reporting more vaccine hesitancy and higher adverse reactions than men [ 47 - 49 ]. Our results support the accuracy of self-reported vaccination data from both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Sex and gender are important factors in understanding the real-world effectiveness of vaccines and postmarketing safety monitoring [ 45 , 46 ]. Sex and gender differences in vaccine hesitancy and immunization outcomes have been observed for COVID-19 and other vaccine-preventable diseases, with women typically reporting more vaccine hesitancy and higher adverse reactions than men [ 47 - 49 ]. Our results support the accuracy of self-reported vaccination data from both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence of sex and gender related differences emerged once the vaccines were used outside trials. When vaccines began to be available to priority populations (healthcare workers) in early 2021, there were early reports of rare allergic reactions to mRNA vaccines and of thrombosis associated with viral vector vaccines, especially in women 722. Early post-vaccination survey reports from the UK and US also suggested that females reported more non-serious side effects than males 2324.…”
Section: Sex and Gender Gaps In Covid-19 Vaccine Researchmentioning
confidence: 99%
“…Countering gaps in sex related data and other dynamics of gender inequality can be good for business. Companies that work to address these issues can be perceived as socially conscious and responsive to user needs and preferences by target consumers, investors, and health payers 7. For example, the market for “femtech”—health technologies such as wearable devices and phone apps to monitor menstruation and fertility, discreet and comfortable breast pumps, and menstrual health products—is expected to grow to about $1tn by 2026 40.…”
Section: Realising the Market Oriented Potential Of Sex And Gendermentioning
confidence: 99%
See 2 more Smart Citations